Pathways to net zero : A comparative study of climate goals and strategies of a prominent Finnish companies - Kalburgi, Ravikumar (2023)
With the global push for carbon neutrality gaining momentum, it is crucial to understand the strategies and actions taken by companies to set and achieve their climate goals. The objective of this research is to document and compare the climate pathways of nine prominent Finnish companies using the foundation framework of Science Based Targets initiatives (SBTi) as a conceptual framework. The companies are Nordea Bank, Sampo, Nokia, Fortum, Neste, UPM-Kymmene, Stora Enso, Kone, and Kesko. The study also aims to investigate the role of offsetting in the companies’ climate goals. The study begins with a background discussion on carbon neutrality and its significance in addressing the challenges posed by climate change. The research questions driving this study aim to explore the measures adopted by the companies, the scope of these measures, reporting frameworks, and sustainability governance incorporated to achieve their climate goals. Data was systematically collected from company sustainability and annual reports. The data analysis employed a theory and content-driven analysis approach, allowing for a comprehensive examination of company actions, reasoning, and logic in climate goal setting. The collected data was compared against the SBTi foundation framework, which offers a rigorous set of requirements and validation protocols for comparing the quality and transparency of climate goals. The main results of the study showcase the diversity of climate objectives and pathways adopted by the selected companies and shed light on the role of offsetting in company climate goals. These companies demonstrated a comprehensive approach to addressing climate change by actively contributing to the global transition towards a net-zero economy. Furthermore, the study investigated the reporting mechanisms and governance structures implemented by the companies. The involvement of companies in carbon offsetting initiatives was examined to understand their relevance to achieving climate goals. Overall, this research contributes to understanding the climate goals of prominent Finnish companies in the context of carbon neutrality and net zero. The findings highlight the strengths and weaknesses of the climate objectives of Finnish companies and their alignment with the Paris Agreement. The qualitative research approach employed in this study enabled a comprehensive exploration and comparison of the climate goals, shedding light on their contributions to the transition towards a sustainable future.